Representative Democracy and Constitution Pancasila Perspective with the 1945 Constitution - Patarai, Muhammad Idris (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The process of receiving aspirations has several pathways or mechanisms, it can be at the time of research, it can be the mechanism for receiving aspirations in the parliament building from or from the mass media, social media, it can also be from the political infrastructure, namely the political parties from which they come, from interest groups or pressure group. The legislature is relatively busy and has a solid agenda of activities and therefore the members in it should ideally have adequate capacity and competence for their duties and functions. The duties and functions of representing the people have been carried out at the time of his representative inauguration as a member of parliament. His authority to choose the chief executive apart from increasing his authority and charisma as a representative of the sovereign people; also at the same time means not returning some of its functions and authorities which have been handed over and received from the people in the general election. This is where the confusion of the direct executive leadership election system, both in the presidential and regional elections. It is even worse when viewed in terms of the constitution, in this case, the source of law which abstracts the empirical values contained in the preamble of the constitution (the Preamble) or the basic values (intrinsic) which are the philosophy as well as the basis of the state, namely Pancasila. In the 4th (fourth) precept, it expressly reads: "Popularity Led by Wisdom of Wisdom in Deliberation/ Representation", but its existence in the Body (article 1 paragraph 2) of the 1945 Constitution of the Unitary State of the Republic of Indonesia is implied and hidden.